2007
DOI: 10.1021/ar600028s
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel Methods for the Assembly of Metal Chalcogenide Quantum Dots

Abstract: Sol-gel chemistry represents a powerful method for assembling metal chalcogenide quantum dots into 3D connected architectures without the presence of intervening ligands to moderate particle-particle interactions. Wet gels prepared by the oxidative loss of thiolate surface groups from chalcogenide nanoparticles can be converted to xerogels (low porosity) or aerogels (high porosity), and the quantum-confinement effects in these low-dimensional networks decrease with increasing density of the network. In this Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
195
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(200 citation statements)
references
References 57 publications
3
195
0
2
Order By: Relevance
“…, Se; R = organic group) are useful 1) as starting materials for metal chalcogenide nanoparticles, [5] 2) as synergist agents of CMPO or DTPA to improve An III / Ln III separation in nuclear waste remediation, [6] 3) for preparing molecular complexes with P-chalcogen ligands [7] and 4) in chalcogen-transfer reactions.…”
Section: Pe Rp(e)a C H T U N G T R E N N U N G (Esime 3 ) 2 {Rp(e)mentioning
confidence: 99%
“…, Se; R = organic group) are useful 1) as starting materials for metal chalcogenide nanoparticles, [5] 2) as synergist agents of CMPO or DTPA to improve An III / Ln III separation in nuclear waste remediation, [6] 3) for preparing molecular complexes with P-chalcogen ligands [7] and 4) in chalcogen-transfer reactions.…”
Section: Pe Rp(e)a C H T U N G T R E N N U N G (Esime 3 ) 2 {Rp(e)mentioning
confidence: 99%
“…[33] Die Synthese von kolloidalen Metallnanopartikeln sowie die Einstellung ihrer Größe, Form und Zusammensetzung ist heutzutage ein umfassend entwickeltes Forschungsgebiet. [34][35][36][37][38][39] Für die Gelbildung werden zahlreiche Methoden zur langsamen Destabilisierung, die bereits zuvor bei Gelen auf Basis von Metallchalkogenidpartikeln Anwendung fanden, [9,13] systematisch für wässrige kolloidale Lösungen von Gold-, Silber-und Platin-Nanopartikeln untersucht. Überkritische Trocknung [2,40] der Hydrogele unter Verwendung von flüssigem CO 2 liefert letztendlich die Aerogele.…”
unclassified
“…These 2D materials, like graphene, have generated a lot of interest due to their exceptional properties for applications such as catalysis, energy storage, sensors, and electronics. [125][126][127] Although there are a number of reports on chalcogels, [128][129][130][131][132] examples of pure TMD aerogels remain limited. 133 In 2015, Worsley et al 18 reported a fairly straightforward method for MoS 2 and WS 2 aerogels.…”
Section: Transition Metal Dichalcogenide Aerogelsmentioning
confidence: 99%